Demographic Trends in Korean Native Cattle Explained Using Bovine SNP50 Beadchip - Aditi Sharma; Dajeong Lim; Han-Ha Chai; Bong-Hwan Choi; Yongmin Cho (Genomics & Informatics, 2016)
Linkage disequilibrium (LD) is the non-random association between the loci and it could give us a preliminary insight into the genetic history of the population. In the present study LD patterns and effective population size (Ne) of three Korean cattle breeds along with Chinese, Japanese and Mongolian cattle were compared using the bovine Illumina SNP50 panel. The effective population size (Ne) is the number of breeding individuals in a population and is particularly important as it determines the rate at which genetic variation is lost. The genotype data in our study comprised a total of 129 samples, varying from 4 to 39 samples. After quality control there were ~29,000 single nucleotide polymorphisms (SNPs) for which r2 value was calculated. Average distance between SNP pairs was 1.14 Mb across all breeds. Average r2 between adjacent SNP pairs ranged between was 0.1 for Yanbian to 0.3 for Qinchuan. Effective population size of the breeds based on r2 varied from 16 in Hainan to 226 in Yanbian. Amongst the Korean native breeds effective population size of Brindle Hanwoo was the least with Ne = 59 and Brown Hanwoo was the highest with Ne = 83. The effective population size of the Korean cattle breeds has been decreasing alarmingly over the past generations. We suggest appropriate measures to be taken to prevent these local breeds in their native tracts.